3T multiparametric MRI of the prostate: Does intravoxel incoherent motion diffusion imaging have a role in the detection and stratification of prostate cancer in the peripheral zone?. Issue 4 (April 2016) - Valerio, Mariacristina; Zini, Chiara; Fierro, Davide; Giura, Francesca; Colarieti, Anna; Giuliani, Alessandro; Laghi, Andrea; Catalano, Carlo; Panebianco, Valeria
Highlights: ADC and D were significantly reduced in PCa compared to PZ tissues. D * was significantly increased in PCa compared to PZ tissues. f were not significantly different between PCa and PZ tissues. The use of T2-weighted imaging/DWI and IVIM improves the PCa diagnostic accuracy. D could be a useful index to distinguish low from intermediate/high-grade tumors. Abstract: Purpose: To evaluate the potential added value of the intravoxel incoherent motion model to conventional multiparametric magnetic resonance protocol in order to differentiate between healthy and neoplastic prostate tissue in the peripheral zone. Material and methods: Mono-exponential and bi-exponential fits were used to calculate ADC and IVIM parameters in 53 patients with peripheral zone biopsy proved tumor. Inferential statistics analysis was performed on T2, ADC and IVIM parameters ( D, D *, f ) comparing healthy and neoplastic tissues. Linear discriminant analysis was performed for the conventional parameters (T2 and ADC), the IVIM parameters (molecular diffusion coefficient ( D ), perfusion-related diffusion coefficient ( D *), and perfusion fraction ( f ) and the combined T2-weighted imaging/DWI and IVIM parameters (T2, ADC, D, D * and f ). A correlation with Gleason scores was achieved. Results: The values of T2, ADC and D were significantly lower in cancerous tissues (2749.82 ± 1324.67 ms, 0.76 ± 0.27 × 10 −3  mm 2 /s and 0.99 ± 0.38 × 10 −3  mm 2 /s respectively) compared to those found in the healthy tissues (3750.70 ± 1735.37 ms, 1.39 ± 0.48 × 10 −3  mm 2 /s and 1.77 ± 0.36 × 10 −3  mm 2 /s respectively); D * parameter was significantly increased in neoplastic compared to healthy tissue (15.56 ± 12.91 × 10 −3  mm 2 /s and 10.25 ± 10.52 × 10 −3  mm 2 /s respectively). The specificity, sensitivity and accuracy of the T2-weighted imaging/DWI and IVIM parameters were 100, 96 and 98%, respectively, compare to 88, 92 and 90% and 96, 92 and 94 for T2-weighted imaging/ADC and IVIM alone. Conclusions: IVIM parameters increase the specificity and sensitivity in the evaluation of peripheral zone prostate cancer. A statistical difference between low grade tumors and high grade tumors has been demostrated in that ADC, D and D * dataset; in particular, D has been found to have the highest significativity.